Effectiveness analysis of water-sealing for underground LPG storage. (January 2016) - Lin, Fang; Ren, Feng; Luan, Hebing; Ma, Guowei; Chen, Shougen
Highlights: We analyse seepage field of the underground petroleum storage project in China. The 3D discrete fracture pipe network model of the developed transient UPNM is adopted. One connectivity evaluation criteria is developed to determine the effectiveness of water-sealing system in the field. Optimal water curtain system design is recommended. Water-sealing performances of different water curtain system schemes with various fracture networks are discussed. Abstract: With the developed transient UPNM, numerical simulations are carried out to analyse the seepage field of the underground petroleum storage project in Jingzhou, China. The 3D discrete fracture pipe network model is adopted to systematically analyse the effects of the water curtain system (different water curtain states, water curtain pressure, length and spacing and the angles of the horizontal water curtain system) on the water-sealing effectiveness of the rock caverns in the fractured rock mass in both construction phase and storage phase. Water-sealing performances of different water curtain system schemes with various fracture networks are also discussed. It is found that the effect of the horizontal water curtain is more important than the vertical water curtain. The reducing of the pressure of the water curtain, the length of the water curtain boreholes and the increase of the spacing of the water curtain borehole can deteriorate the seal effect of the water curtain, increase of angles of horizontal water curtain can't improve water seal. And effective connectivity of fractures is found to be dominant factor to determine water-sealing results. In addition, it is worth mentioning that the fracture network is highly irregular in the flow domain, which greatly influence the seepage field, and the failure of the water seal effect can occur locally. The locally connected unsaturated flow paths have been observed in the study, which cannot be found by using the continuous simulation model. Finally, optimal water curtain system design is recommended. Furthermore, one connectivity evaluation criteria is developed to determine the effectiveness of water-sealing system in the field, according to Lugeon, effectiveness and TEM site test.